Steel rebar corrosion and corrosion-induced cracking in reinforced foamed concrete - Luo, Yongheng; Zhu, Qilin; Chen, Depeng; Liu, Chunlin; Pan, Suiwei (Frontiers in Materials, 2022)
This study investigated the corrosion behavior of steel rebar in foamed concrete and the effects of water-cement ratio, fly ash, and fiber on reinforced foamed concrete's corrosion rate and crack width. It was found that the corrosion rate of steel rebar and crack width of foamed concrete increased slowly with time and then developed rapidly, finally growing slowly. The higher the density of foamed concrete, the stronger the corrosion resistance of steel rebar. The best corrosion resistance of steel rebar in foamed concrete is achieved when the water-cement ratio is 0.5, fly ash and fiber are 20% and 0.6%, respectively.